(3GdJHUQI aj Yde GdgjFIs - (3CHh eMeO YHO GdLHGQ Hf YHO GdLHGQ Hf eMeO GdKGHJj GdNQbj,J (B553 (3g` s ((3YHO Gddg Hf eMeO Hf ESeGYjd Hf CMeO Hf GdCcHQ GdTGaYi s)
(3ChdgG (B:s
(3GdMeO ddg Mb MeOg hHYO , aEf GdYdeGA hGdMceGA cGfhG bHd ReGffG gPG eJhaQjf Ydi LejY GdYdhe hGdBf abO fGeJ Shb GdYde hHGQJ hCdaJ gPG GdcJGH ai Yde GdgjFI s
(3BNQgG (B:s
(3hGdefLehf jbSehf cd SGYI ef GdSGYGJ HSJjf bSekG , cd bSe ObjbI , Ydi eG OGQJ YGOI ai bSeI GdHQhL hCLRGFgG HGdCLRGA GdSJjfjI adfNJe GdcJGH , EPG GJjfG HGdehYhO Ydi MSH GdebOhQ (B, (3hdhGgH GdYbd GdMeO HdG fgGjI s
(3HgG LOGhd hQShe gfOSjI hadcjIs
(3fSNI KGdKIs
(3JJab ai ChdgG hBNQgG eY GdfSNI GdChdi HGNJdGa ai HYV GdCdaGXs
(3cJHJ Hbde eged GdfbW CMjGfkG s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
Keywords: (3Gdadcs